ORGANIZATIONAL BEHAVIOR IN SMART ORGANIZATIONS - Rautrao, Revati Ramrao (Interdisciplinary Social Studies, 2023)
Background: Organizational behavior affects job performance, worker interaction, job commitment, leadership, and social control designs. Human behavior in an exceedingly work atmosphere determines its impact on job structure, performance, communication, motivation, leadership, etc. Aim: The research would like to understand and predict structure life, and get concerned to profit their organization may be a prime concern in reaching strategic goals by encouraging workers. Method: The study has completely captured a review of earlier studies relating OB by relating totally different international and national journals and studies conducted by different people at different periods. Findings: Companies that supply smart worker edges which have friendly conditions square measure a lot of profitable than those who square measure less people-oriented. The contemporary organizations notice that to achieve success and to stay competitive, it is imperative to rely on info technology (IT) and to use trendy management practices.